Synthesis, characterization, and anticancer activity of ferrocenyl complexes bearing different organopalladium fragments. (16th February 2022) - Scattolin, Thomas; Moro, Giulia; Serena, Anita; Guadagnin Pattaro, Alessia; Rizzolio, Flavio; Canzonieri, Vincenzo; Demitri, Nicola; Bortolamiol, Enrica; Moretto, Ligia Maria; Visentin, Fabiano
Abstract : A straightforward synthetic route to a selection of new ferrocenyl complexes bearing different organopalladium fragments is reported. The target complexes were fully characterized by Nuclear Magnetic Resonance, High Resolution Mass Spectrometry, Infrared Spectroscopy, X‐ray Diffraction, and electrochemical techniques. All compounds, with the exception of Pd(0)‐olefin derivatives, showed excellent antitumor activity on ovarian cancer cells and, in the case of Pd (II)‐allyl and Pd (II)‐butadienyl complexes, a lower cytotoxicity towards normal cells. Abstract : Ferrocenyl‐organopalladium complexes: The synthesis and characterization of novel ferrocenyl complexes bearing different organopalladium fragments are reported. All compounds, with exception of Pd(0)‐olefin derivatives, showed excellent antitumor activity on different cancer cell lines.